Penggunaan Aplikasi Ibis Paint X Bagi Mahasiswa Dalam Berkarya Seni Zaman Sekarang - M. Faiz; Sabrina Azlianty; Haniah Zuhro Ginting; Jelli Br Togatorop; Lia Sofianna Br Saragih; Romauli Panjaitan; Lili Tansliova (Pusat Riset dan Inovasi Nasional, 2024)
In the current digital era, creative applications have become essential tools for art students to express their creativity. One popular application is Ibis Paint X, which offers various features for digital drawing and painting. This research aims to investigate the use of the Ibis Paint X application by art students in creating art in today's era. The research method employed is an online survey distributed to art students from various educational institutions. Data were analyzed using a qualitative approach to understand how the application is used, its strengths, and weaknesses in the context of students' art. The research findings indicate that the Ibis Paint X application is widely used by art students to create digital artworks. Features such as various brush types, layers, and effects allow students to experiment with different styles and techniques. However, some students also encounter challenges in operating this application, particularly in terms of the complexity of the user interface and limitations in its free version.